ASUHAN KEBIDANAN KOMPREHENSIF PADA IBU R DENGAN PENERAPAN MEDITASI DAN AFIRMASI POSTIF UNTUK MENGURANGI KECEMASAN PERSALINAN - Ulfa, Muetia; Norisa, Nanda; Julianti, Rina; Zahara, Evi (SINERGI : Jurnal Riset Ilmiah, 2025)
Introduction: Maternal Mortality Rate (MMR) in Indonesia is still higher than ASEAN countries to achieve the SDGs target of less than 70 maternal deaths per 100,000 live births in 2030. Early detection efforts to overcome morbidity and mortality for both mothers and babies can be done by implementing continuous care starting from pregnancy to postpartum without any complications. Pregnant women with anxiety need complementary care that can make mothers relax and calm in facing their labor. One application that can be done is meditation and positive affirmations.  Purpose: This study aims to provide comprehensive midwifery care, especially for pregnant women in the third trimester who experience anxiety before giving birth through the application of meditation and positive affirmations.  Research method: This study is a case study with a qualitative descriptive approach. The study was conducted by exploring and providing comprehensive midwifery care to Mrs. R G3P2A0 starting from the third trimester of pregnancy to postpartum. While for maternal anxiety using the HARS questionnaire instrument.Research results: Comprehensive midwifery care for Mrs. R has been carried out from pregnancy to postpartum. In the third trimester of pregnancy care based on the results of the anamnesis, it was found that the mother experienced anxiety in facing childbirth, so an anxiety assessment was carried out using the HARS questionnaire, the results showed that the mother experienced moderate anxiety. Meditation and positive affirmations were applied for 10 minutes every 2 visits and the results showed a reduction in anxiety. In addition, midwifery care for mothers giving birth to Mrs. R lasted for approximately 1 hour, the care provided was to repeat the meditation technique and positive affirmations for 10 minutes, after which there was a reduction in anxiety. Midwifery care for Mrs. R's baby was carried out 1 visit and no gaps were found between the theory and the care provided. Postpartum midwifery care given to Mrs. R was carried out 2 visits and no gaps were found between the theory and the care provided. Conclusion: Midwifery care provided to Mrs. R from the third trimester of pregnancy to postpartum can be carried out well. Anxiety experienced before childbirth can be overcome by applying meditation and positive affirmations, which results in reducing the anxiety felt by the mother during childbirth. Meanwhile, newborn and postpartum care went well and without obstacles